A rare clinical case of surgical treatment of amyand's hernia in a preterm newborn baby - O. K. Sliepov; M. V. Ponomarenko; O. V. Markevich; O. S. Skiba; O. G. Shipot (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2019)
For citation: Sliepov OK, Ponomarenko MV, Markevich OV, Skiba OS, Shipot OG. (2019). A rare clinical case of surgical treatment of Amyand's hernia in a preterm newborn baby. Paediatric Surgery. Ukraine. 3(64): 42-46. doi 10.15574/PS.2019.64.42 Article received: May 08, 2019. Accepted for publication: Sep 15, 2019. The article presents a rare clinical case of surgical treatment of a premature newborn baby with a birth defect - the right Amyand's hernia. One-stage radical surgical treatment was performed: appendectomy and right-sided inguinal hernia repairing. The result of the surgical correction of the presented malformation is good. After treatment the child recovered. The research was carried out in accordance with the principles of the Helsinki Declaration. The study protocol was approved by the Local Ethics Committee (LEC) of an participating institution. The informed consent of the patient was obtained for conducting the studies. No conflict of interest was declared by the authors.